2019
DOI: 10.1088/1755-1315/288/1/012110
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass exchange packing with adjustable parameters for absorption and evaporation cooling

Abstract: Data of experimental study of hydrodynamics, heat and mass transfer of packing with adjustable parameters and some comparative characteristics of the packed device with packing, which have wide industrial application, are given in the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The packing material studied in this work due to its rigid structure and tight packing has constant structural characteristics and is of very little sensitivity to volumetric deformation. It should be noted that many samples of packing materials have volume elastic properties and can be sensitive to volumetric deformation and control of hydrodynamic regimes [39][40][41][42] during operation which opens up unique possibilities for manufacturing universal mass transfer contact devices with the possibility of effectively influencing the quality of mass transfer processes, the degree of purification of liquid and gas heterogeneous systems and the concentration of the final products of mass transfer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The packing material studied in this work due to its rigid structure and tight packing has constant structural characteristics and is of very little sensitivity to volumetric deformation. It should be noted that many samples of packing materials have volume elastic properties and can be sensitive to volumetric deformation and control of hydrodynamic regimes [39][40][41][42] during operation which opens up unique possibilities for manufacturing universal mass transfer contact devices with the possibility of effectively influencing the quality of mass transfer processes, the degree of purification of liquid and gas heterogeneous systems and the concentration of the final products of mass transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The packing elements are of a spiral structure and have fins and micro-roughness on their surface due to plastic deformations of the metal being treated after contact with the cutter. Experimental studies have shown that such geometric features of metal shavings samples (packing elements) provide the development of hydromechanical regimes and the intensification of mass transfer processes [39,40]. These are exactly the properties which are desired to be developed while studying new mass transfer contact devices but in this case they are generated naturally as industrial wastes appearing in large quantities at machine-building enterprises during the mechanical processing of metals by cutting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Automatic sectional adjustment of catalyst layers allows adjusting the system with the high-precision and influencing the chemical reactions directly in the process. To implement automatic adjustment catalysts are required to have volume elastic properties [31][32][33][34]. In addition, the catalyst should provide a developed contact surface with reaction products, and the reaction mass, in turn, should actively wash the surface of the catalyst giving an impulse to a chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the catalyst should provide a developed contact surface with reaction products, and the reaction mass, in turn, should actively wash the surface of the catalyst giving an impulse to a chemical reaction. All these requirements are accumulated in the catalysts layers in the form of pressed sections of metal shavings (metalworking machine wastes) [31][32][33][34][35][36][37][38][39][40][41]. Moreover, the shaving materials themselves can be catalysts or catalysts can be applied to their developed ornate surface.…”
Section: Introductionmentioning
confidence: 99%